Program Manajemen Kesiswaan Dalam Mengembangkan Bakat Minat Peserta Didik di MA Ma’arif NU Kepung - Suwarno (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Education is an attempt to improve human thinking, maturity, and behaviour. Education changes the mindset of humans for the better, therefore every humanbeing is entitled to an education. Various educational institutions strive to provide the best educational services to develop science and student achievement. In this case, student management has a very important role in improving the achievement, learning ability, talent and ability of learners and coaching in order to improve the thinking power of learners both in academic and non-academic fields. When viewed from the data source, this study uses primary data and sounder data. While the type of data, the approach used includes qualitative research that produces descriptive data, data collection techniques in this study using three techniques, namely interviews, observations, and documentation to the parties concerned.